Influence of sulfuric acid concentration on the surface roughness of titanium alloy plates - Fantastika, Adela Dayu; Suwandi, Trijani; Putri, Tansza Setiana (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
The surface roughness of an implant material (titanium alloy) is an important factor in optimizing osseointegration. Various efforts have been made to optimize the roughness of implant materials, such as acid etching. Previous research showed etching with sulfuric acid ((H2SO4)) at a temperature of 60 °C for 60 minutes could increase roughness. However, further research is needed regarding the concentration of H2SO4 that can optimize surface roughness. This research aimed to determine the concentration of H2SO4 that can be used to obtain optimal roughness. This study used a pre-test and post-test group design by immersing titanium alloy plates in a solution of saline water (negative control), 12.17 M HCl (positive control), and (H2SO4) at various concentrations, namely 6.94 M, 9 M, and 11.06 M for 60 minutes at 60 °C. Next, a surface roughness test and Scanning Electron Microscopy (SEM) were carried out. The research results were analyzed statistically using the Shapiro-Wilk, Wilcoxon, Kruskal-Wallis, and Mann-Whitney tests. The results showed that in the (H2SO4) group, there were significant differences before and after treatment (p < 0.05). The higher the concentration of (H2SO4) used, the higher the surface roughness value. The SEM test showed that the group with a higher (H2SO4) concentration had a rougher topography and more visible grooves. In conclusion, etching with (H2SO4) can increase the surface roughness of titanium alloys, and (H2SO4) at a concentration of 11.06 M led to the highest roughness value in this study.